Innate Immunity to Spiral Ganglion Neuron Loss: A Neuroprotective Role of Fractalkine Signaling in Injured Cochlea - Stothert, Andrew Rigel; Kaur, Tejbeer (Frontiers in Cellular Neuroscience, 2021)
Immune system dysregulation is increasingly being attributed to the development of a multitude of neurodegenerative diseases. This, in large part, is due to the delicate relationship that exists between neurons in the central nervous system (CNS) and peripheral nervous system (PNS), and the resident immune cells that aid in homeostasis and immune surveillance within a tissue. Classically, the inner ear was thought to be immune privileged due to the presence of a blood-labyrinth barrier. However, it is now well-established that both vestibular and auditory end organs in the inner ear contain a resident (local) population of macrophages which are the phagocytic cells of the innate-immune system. Upon cochlear sterile injury or infection there is robust activation of these resident macrophages and a predominant increase in the numbers of macrophages as well as other types of leukocytes. Despite this, the source, nature, fate and functions of these immune cells during cochlear physiology and pathology remains unclear. Migration of local macrophages and infiltration of bone-marrow derived peripheral blood macrophages into the damaged cochlea occur through various signaling cascades, mediated by release of specific chemical signals from damaged sensory and non-sensory cells of the cochlea. One such signaling pathway is CX3CL1-CX3CR1, or fractalkine (FKN) signaling, a direct line of communication between macrophages and sensory inner hair cells (IHCs) and spiral ganglion neurons (SGNs) of the cochlea. Despite the known importance of this neuron-immune axis in CNS function and pathology, until recently it was not clear whether this signaling axis played a role in macrophage chemotaxis and SGN survival following cochlear injury. In this review, we will explore the importance of innate immunity in neurodegenerative disease development, specifically focusing on the regulation of the CX3CL1-CX3CR1 axis, and present evidence for a role of FKN signaling in cochlear neuroprotection.